FAKTOR-FAKTOR YANG MEMPENGARUHI PEMANFAATAN POSBINDU KESEHATAN WANITA USIA SUBUR - Wirata, Resta Betaliani; Istianti, Daning Widi (STIKES Bethesda Yakkum, 2020)
Background: Women's health is an example of public health. A container that can be used by women of childbearing age in detecting, understanding, obtaining and applying health measures, one of which is an integrated posted cooperation or Posbindu. Many posbindu members who have not been attended routinely in Posbindu activities because of several factors that affect. According to health staff assitent, stated that if knowledge, posbindu activities, attitudes, mileage, and family support are things that affect posbindu participants attending in the activity. Objective: This study aims to determine the factors that influence the utilize of Posbindu in Posbindu Apsari in RW 10 Bumijo, Jetis, Yogyakarta. Methods: The design used in this study is a quantitative research design with analytic survey methods. This study uses a cross sectional approach. Results: This study found that the mileage factor has a relationship with the utilize of Posbindu with p-value were 0,000. While the knowledge, posbindu activities, attitudes, and family support as others factors were not significant relationship to the utilize of posbindu. Conclusion: The mileage factor has a significant relationship with the utilize of Posbindu with p-value were 0,000. Suggestion: The mileage factor that has a significant relationship to the utilize of Posbindu needs to be considered and followed up then could make that all members of the Posbindu Apsari can attend regularly.